Quantitative interpretation of PF4/heparin‐EIA optical densities in predicting platelet‐activating VITT antibodies. (4th September 2022) - Schönborn, Linda; Thiele, Thomas; Esefeld, Max; El Debuch, Khalil; Wesche, Jan; Seck, Sabrina E.; Kaderali, Lars; Wolff, Martina; Warkentin, Theodore E.; Greinacher, Andreas
Abstract: Background: Vaccine‐induced immune thrombotic thrombocytopenia (VITT) is a prothrombotic, heparin‐induced thrombocytopenia (HIT)‐mimicking, adverse reaction caused by platelet‐activating anti‐platelet factor 4 (PF4) antibodies that occurs rarely after adenovirus vector‐based COVID‐19 vaccination. Strength of PF4‐dependent enzyme immunoassay (EIA) reactivity—judged by optical density (OD) measurements—strongly predicts platelet‐activating properties of HIT antibodies in a functional test. Whether a similar relationship holds for VITT antibodies is unknown. Objectives: To evaluate probability for positive platelet activation testing for VITT antibodies based upon EIA OD reactivity; and to investigate simple approaches to minimize false‐negative platelet activation testing for VITT. Methods: All samples referred for VITT testing were systematically evaluated by semiquantitative in‐house PF4/heparin‐EIA (OD readings) and PF4‐induced platelet activation (PIPA) testing within a cohort study. EIA‐positive sera testing PIPA‐negative were retested following 1/4 to 1/10 dilution. Logistic regression was performed to predict the probability of a positive PIPA per magnitude of EIA reactivity. Results: Greater EIA ODs in sera from patients with suspected VITT correlated strongly with greater likelihood of PIPA reactivity. Of 61 sera (with OD values >1.0) testing negative in the PIPA, a high proportion (27/61, 44.3%) became PIPA positive when tested at 1/4 to 1/10 dilution. Conclusions: VITT serology resembles HIT in that greater EIA OD reactivity predicts higher probability of positive testing for platelet‐activating antibodies. Unlike the situation with HIT antibodies, however, diluting putative VITT serum increases probability of a positive platelet activation assay, suggesting that optimal complex formation depends on the stoichiometric ratio of PF4 and anti‐PF4 VITT antibodies.